# SBP-Program

## Multiplying monomials with different exponents

How to multiply monomials with different exponents? How do you multiply monomials with different exponents?

### Examples of multiplying monomials with different exponents

Example of multiplying monomials with different exponents.

Multiply the following monomials with different exponents

15x2 * 2x

Solution.

15x2 * 2x =
15x2 * 2x1 =
(15 * 2) * (x2 * x1) =
(30) * (x2 + 1) = 30x3

Example of multiplying monomials with different exponents.

Multiply the following monomials with different exponents

10y2z * 5yyz

Solution.

10y2z * 5yyz =
10y2z1 * 5y1y1z1 =
10y2z1 * 5y1 + 1z1 =
10y2z1 * 5y2z1 =
(10 * 5) * (y2 * y2) * (z1 * z1) =
(50) * (y2 + 2) * (z1 + 1) =
50y4z2

Example of multiplying monomials with different exponents.

Multiply the following monomials with different exponents

6a * 6ab2

Solution.

6a * 6ab2 =
6a1 * 6a1b2 =
(6 * 6) * (a1 * a1) * b2 =
(36) * (a1 + 1) * b2 =
36a2b2

Example of multiplying monomials with different exponents.

Multiply the following monomials with different exponents

28y4 * 2y3 * y2

Solution.

28y4 * 2y3 * y2 =
(28 * 2) * (y4 * y3 * y2) =
(56) * (y4 + 3 + 2) =
56y9